2021
DOI: 10.3389/fcimb.2021.624650
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Single Cell Analyses of the Nutritional Environment of Intracellular Salmonella enterica

Abstract: The facultative intracellular pathogen Salmonella enterica Typhimurium (STM) resides in a specific membrane-bound compartment termed the Salmonella-containing vacuole (SCV). STM is able to obtain all nutrients required for rapid proliferation, although being separated from direct access to host cell metabolites. The formation of specific tubular membrane compartments, called Salmonella-induced filaments (SIFs) are known to provides bacterial nutrition by giving STM access to endocytosed material and enabling p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 76 publications
(105 reference statements)
0
16
0
Order By: Relevance
“…Primary human macrophages were prepared from buffy coat from pooled blood samples of anonymous donors (obtained from the Deutsches Rotes Kreuz) as described in Bonifacino, Dasso, Harford, Lippincott‐Schwartz, and Yamada (2004) and in Röder, Felgner, and Hensel (2021). Preparation of lymphocytes by Ficoll–Hypaque gradient was performed as described, alternatively to whole blood, buffy coat was mixed 1 + 1 with PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary human macrophages were prepared from buffy coat from pooled blood samples of anonymous donors (obtained from the Deutsches Rotes Kreuz) as described in Bonifacino, Dasso, Harford, Lippincott‐Schwartz, and Yamada (2004) and in Röder, Felgner, and Hensel (2021). Preparation of lymphocytes by Ficoll–Hypaque gradient was performed as described, alternatively to whole blood, buffy coat was mixed 1 + 1 with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…At various time points ranging from 2 to 24 hr p.i., host cells were lysed by addition of 0.1% Triton X‐100 in PBS and fixed with 3% PFA for subsequent FC analyses using the Attune NxT Cytometer (Thermo Fischer). Further details on gating strategies and quantification of populations size and expression levels can be found in prior reports (Röder, Felgner, & Hensel, 2021; Röder & Hensel, 2020; Schulte et al, 2021). Experiments were performed in triplicates at least three times.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, bioavailability of iron in the gastrointestinal milieu can be extremely low and depends on high affinity iron acquisition to allow efficient colonization by Salmonella in both mice and chicken models. Findings from a recent attempt to analyze nutrient requirements for growth of intracellular STm during infection using HeLa epithelial cells suggested the presence of two populations of Salmonella with distinct demands for iron and manganese ( Röder et al, 2021 ). In that study, the cytosolic fraction of STm showed hyper-replication compared to vacuolar Salmonella and this correlated with stronger induction of the sitABCD promoter during infection ( Röder et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…If required, the aph cassette was removed by introduction of pE-FLP and FLP-mediated recombination. Plasmid p5633 as reporter for expression of sifA was generated by Gibson assembly for exchange of P uhpT in p4889 by a 300 bp PCR fragment containing P sifA , basically as described before [ 27 , 50 ]. Plasmids used in this study are listed in Table 2 and were introduced into various WT and mutant strains by electroporation.…”
Section: Methodsmentioning
confidence: 99%
“…CRL-1593.2) was cultured in RPMI-1640 medium (Merck) supplemented with 10% iFCS. Human primary macrophages were generated from monocytes isolated from buffy coat as previously described [ 50 ], and cultured in RPMI-1640 medium supplemented with 20% iFCS. Under these conditions, predominantly M1-polarized macrophages were obtained.…”
Section: Methodsmentioning
confidence: 99%